Acid-induced Zn(ii)-based metal–organic frameworks for encapsulation and sensitization of lanthanide cations. Issue 11 (17th February 2015) - He, Hongjie; Zhang, Lina; Deng, Mingli; Chen, Zhenxia; Ling, Yun; Chen, Jinxi; Zhou, Yaming
Abstract : Two Zn(ii )-based metal–organic frameworks with different coordination geometries have been synthesized and one can effectively capture metal cations and sensitize the visible-emitting Tb 3+ . Abstract : Two Zn(ii )-based metal–organic frameworks, namely, [Zn3 (Hbptc)2 (DMF)2 ]·2DMF(1 ) and [Zn5 (bptc)3 (H2 O)]((CH3 )2 NH2 )2 (2 ), (H4 bptc = 3, 3′, 5, 5′-biphenyltetracarboxylic acid, DMF = N, N ′-dimethylformamide), have been synthesized using different amounts of nitric acid under mixed-solvothermal conditions.1 and2 display different coordination geometries and donor ligands for the Zn 2+ ions. In1, only three carboxylic acid groups of H4 bptc take part in the construction of the three-dimensional (3-D) framework with Zn 2+, and one remains uncoordinated that can bind to other metal ions. Postsynthetic exchange of1 with Ln 3+ cations demonstrates that1 can effectively capture metal cations and sensitize the visible-emitting Ln 3+ .